Pengembangan Bahan Ajar Bahasa Arab di Sekolah Tingkat Atas - Mohamad Ghozi (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2020)
Teaching material is one of the three Elements of Teaching and Learning activities besides, teachers and students. Without teaching material, it is not possible for teaching and learning activities to proceed properly. Teaching material will be good if given according to the ability of students who use the material. And good material is material that adjusts the development, both intellectual development, student psychology, and the development of the era in which students are located. This Scientific Journal will explain how a teacher can make Arabic teaching materials for his students. There is no need to buy textbooks or worksheets that are not necessarily used when they are suitable with the abilities of their students.